Seyyed Hossein Nasr: Kritik Islam atas Sekularism Lingkungan - Agung Pratama Dharma; Saldan Manufa (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2024)
This article aims to understand Islam's critique of environmental secularism using the thoughts of Seyyed Hussein Nasr. This research is based on qualitative methods with library research. The purpose of using this type of research is to be able to more easily map the topic under study based on literature sources. The main argument in this article is that the presence of the secularism paradigm in the modern era not only creates a spiritual crisis, but also an ecological crisis. Islam with the teachings of moral wisdom contained in the Koran makes a value to minimize environmental damage. The results of the research show that the environmental crisis is an urgent problem for the whole world, including Indonesia. The presence of the modern era with its secular paradigm gave birth to an understanding of the environment that has no sacred value and is only an object of domination for humans. With this understanding there are various environmental crises such as deforestation, plastic waste, air pollution, excessive land use by investors and polluted water. So that it is necessary to build awareness of metaphysical understanding that humans and the environment (universe) are one unit.